Comparison of the Toponomes of Alveolar Macrophages From Wild Type and Surfactant Protein A Knockout Mice and Their Response to Infection - Phelps, David S.; Chinchilli, Vernon M.; Zhang, Xuesheng; Shearer, Debra; Weisz, Judith; Floros, Joanna (Frontiers in Immunology, 2022)
Background: Surfactant protein-A (SP-A) plays a critical role in lung innate immunity by regulating alveolar macrophages (AM), expression of inflammatory mediators, and other host defense proteins. The toponome imaging system (TIS), a serial immunostainer, was used to study the AM toponome because it characterizes the localization of multiple markers and identifies marker combinations in each pixel as combinatorial molecular phenotypes (CMPs). We used TIS to study the AM toponome from wild type (WT) and SP-A knockout (KO) mice and changes following Klebsiella pneumoniae exposure. Methods: WT or KO mice received intratracheal K. pneumoniae or vehicle and AM were obtained by bronchoalveolar lavage after one hour. AM were attached to slides and underwent TIS analysis. Images were analyzed to characterize all pixels. AM CMPs from WT vehicle (n=3) and infected (n=3) mice were compared to each other and to AM from KO (n=3 vehicle; n=3 infected). Histograms provided us with a tool to summarize the representation of each marker in a set of CMPs. Results: Using the histograms and other tools we identified markers of interest and observed that: 1) Both comparisons had conserved (present in all group members) CMPs, only in vehicle AM and only in infected AM, or common to both vehicle and infected AM, (i.e., unaffected by the condition). 2) CMP number decreased with infection in WT and KO versus vehicle controls. 3) More infection-specific CMPs in WT vs KO AM. 4) When AM from WT and KO vehicle or infected were compared, there were more unique CMPs exclusive to the KO AM. 5) All comparisons showed CMPs shared by both groups. Conclusions: The decrease of CMPs exclusive to infected AM in KO mice may underlie the observed susceptibility of KO mice to infection. However, both KO groups had more exclusive CMPs than corresponding WT groups, perhaps indicating a vigorous effort by KO to overcome deficits in certain proteins and CMPs that are dysregulated by the absence of SP-A. Moreover, the presence of shared CMPs in the compared groups indicates that regulation of these CMPs is not dependent on either infection or the presence or absence of SP-A.